Existence and stability of a two-parameter family of solitary waves for a logarithmic NLS–KdV system. (December 2019) - Ardila, Alex H.
Abstract: The aim of this paper is to provide a proof of the existence and (conditional) orbital stability for a two-parameter family of solitary-wave solutions to a coupled system of logarithmic nonlinear Schrödinger–Korteweg–de Vries equations. We also obtain the existence of global solutions for initial data in the energy space H ℂ 1 ( R ) × H 1 ( R ) and in an appropriate Orlicz space.